European club football after "five treatments" with financial fair play: Time for an assessment - Egon Franck (International Journal of Financial Studies, 2018)
UEFA's Club Licensing and Financial Fair Play Regulations (FFP) have impacted European club football. After five distinct applications of the break-even requirement, which represents the cornerstone of these regulations, it is time for an assessment. How has the situation in European top-division football changed since the FFP regulation? The most recent financial data show that European club football is characterized by significant financial recovery and further polarization. How has the FFP regulation presumably affected this development? This article discusses plausible reasons why FFP has contributed to financial recovery but has not aggravated polarization. Understanding the drivers of polarization is essential before taking further regulatory steps.
Keywords: L83; L49; L51; 330; football; regulation; financial fair play; financial recovery; polarization